Caffeine as an Ergogenic Aid: A Literature Review of Mechanisms of Action, Performance Effects and Safety Thresholds - Wojciechowska, Urszula, Justyna; Rafałowicz, Adam; Zajkowska, Izabela (Quality in Sport, 2025)
Abstract Background: Caffeine is the most widely consumed psychoactive substance worldwide, that can be found in coffee, tea, energy drinks, and dietary supplements. Numerous studies have confirmed caffeine’s potential to decrease fatigue and increase performance. However, optimal dosing strategies and safety profiles across diverse athletic populations remain under active investigation. Aim: This study present the current knowledge on the prevalence of caffeine consumption, its physiological mechanisms, its impact on physical performance, and the potential risks associated with its use. Material and methods. A literature review of studies published in the PubMed and Google Scholar databases was conducted, analyzing the prevalence of caffeine intake, its physiological mechanisms, effects on physical performance, and associated harms. Results. Caffeine supplementation, ingested approximately 60 minutes before exercise enhance endurance performance. In strength assessments, caffeine has been found to enhance 1RM (bench press, squat, deadlift). However caffeine also has adverse effects, including tremors, tachycardia, gastrointestinal discomfort and in some cases, cardiac arrhythmias, that can occur at doses exceeding 7 mg/kg. Caffeine metabolism can affected by genetic polymorphism, hormonal modulators and age-related factors, influence caffeine’s half-life and risk of accumulation. Conclusions. Caffeine supplementation at 3–6 mg/kg is an effective and generally safe ergogenic enhancer for increasing endurance and muscular strength. However, the narrow margin between optimal and toxic doses can be different at various population. Future research should focus on long-term safety of caffeine supplementation, the factors of inter-individual variability to caffeine safety and potential interactions with other performance-enhancing compounds.